2020
DOI: 10.1038/s41467-019-13831-w
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics meets proteomics in an epigenome-wide association study with circulating blood plasma protein traits

Abstract: DNA methylation and blood circulating proteins have been associated with many complex disorders, but the underlying disease-causing mechanisms often remain unclear. Here, we report an epigenome-wide association study of 1123 proteins from 944 participants of the KORA population study and replication in a multi-ethnic cohort of 344 individuals. We identify 98 CpG-protein associations (pQTMs) at a stringent Bonferroni level of significance. Overlapping associations with transcriptomics, metabolomics, and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 74 publications
8
59
0
Order By: Relevance
“…NLRC5 acts as a potent regulator of the inflammasome [44,95]. Zaghlool et al showed that altered methylation at the NLRC5 locus associates with several inflammatory markers, including CXCL10 and CXCL11, with pathway analyses linking it to disease states in which NLRC5 dysfunction is implicated such as cancer and cardiovascular disease [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLRC5 acts as a potent regulator of the inflammasome [44,95]. Zaghlool et al showed that altered methylation at the NLRC5 locus associates with several inflammatory markers, including CXCL10 and CXCL11, with pathway analyses linking it to disease states in which NLRC5 dysfunction is implicated such as cancer and cardiovascular disease [43].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also carried out epigenome-wide association studies (EWAS) on the levels of a small set of inflammatory proteins, including C-reactive protein, interleukins-(1β, 4, 6, 9 and 10), interferon-gamma, transforming growth factor-beta and tumour necrosis factor [37][38][39][40][41][42]. Zaghlool et al performed an EWAS of 1123 proteins, which pointed towards networks of chronic low-grade inflammatory biomarkers (n = 944 individuals) [43]. In an integrative approach, Ahsan et al aimed to identify genetic and epigenetic markers associated with protein biomarkers including inflammatory mediators (n ≤ 1033 individuals) [44].…”
Section: Introductionmentioning
confidence: 99%
“…The components were identified based on the extracted raw data using Metabolon's proprietary software. Metabolon's compound annotations and data have been independently validated by many previous studies, including several genetic association studies by our own group 23,47 .…”
Section: Sample Collectionmentioning
confidence: 96%
“…NRLC5 acts as a potent regulator of the inflammasome (40,41). Zaghlool et al showed that altered methylation at the NLRC5 locus associates with several inflammatory markers, including CXCL10 and CXCL11, with pathway analyses linking it to disease states in which NLRC5 dysfunction is implicated such as cancer and cardiovascular disease (9).…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have characterised genetic factors which are associated with circulating inflammatory protein levels (also known as protein quantitative trait loci or pQTLs) (n = 9-83 proteins, 65-6,861 individuals) (6)(7)(8). Zaghlool et al performed an epigenome-wide association study (EWAS) of 1123 proteins, which pointed towards networks of chronic low-grade inflammatory biomarkers (n = 944 individuals) (9). In an integrative approach, Ahsan et al identified epigenetic, as well as genetic, markers associated with protein biomarkers including inflammatory mediators (n ≤ 1,033 individuals) (10).…”
Section: Introductionmentioning
confidence: 99%